RESISTANCE OF ELASTIC TUBES EMPLOYED IN REHABILITATION AND SPORTS TRAINING PROTOCOLS (Fiep Bulletin - online, 2011)
The purpose of this study was to determine the relationship between elastic resistance and durability offered by national elastic tubes Auriflex® - 204 and imported elastic tubes Thera-band® - silver used as source of dynamic progress resistance (DPR) in programs of rehabilitation and sports training. The bodies test have been submitted to axial traction tests at 0, 500, 1000, 2000, 3000 loading-unloading cycle. Each of the respective cycling values consisted of 6 bodies test. The loading-unloading cycle reached a maximum strain of 100% from the initial length and a displacement rate of 1800 mm/min (0.5 Hz) and after each test the bodies test were submitted to 300% of strain to obtain the force curve of the elastic tubes. The results obtained through this study confirm the reports of durability for the reference study of the Thera band® manufacturer. The Auriflex® 204 tubes present maximum force values higher than those of Lengruber® 204 tubes, despite they present the same area of transverse section and the same material, which is due to the methods and polymers employed in their production. The Auriflex® 204 tubes of more accessible cost lose their capacity to respond to the same force values after the cycling, although they can replace other imported tubes of better quality from adjusting to the target load.